Comparison of composite resin and porcelain inlays for restoration of noncarious cervical lesions: An In vitro study - Chee, Hui Theng (Dent Res J (Isfahan), 2018)
BACKGROUND: Composite resin (CR) currently is one of the most commonly used material in restoring noncarious cervical lesions (NCCL) due to its strength and esthetics color but has microleakage problem. The aim of this study is to compare in vitro the microleakage depth between CR and porcelain in restoring NCCL. MATERIALS AND METHODS: This an in vitro study was done by preparing cavities on the buccocervical surface of 62 extracted premolar teeth which randomly assigned to two groups (n = 31) where Group 1 was restored with nanocomposite and Group 2 was cemented with porcelain cervical inlays. They were then subjected to thermocycling before immersion in 2% methylene blue dye for 24 h. Dye penetration depths were measured using Leica imaging system For statistical analysis, independent t-test was used to analyze the results (P < 0.05). RESULTS: Porcelain cervical inlay restorations demonstrated statistically lesser microleakage depth for the cervical margins (P = 0.018) when compared to CR. Deeper microleakage depth at the cervical compared to coronal margins of CR (P = 0.006) but no significant difference of both margins for porcelain cervical inlays (P = 0.600). CONCLUSION: Porcelain cervical inlays show lesser microleakage than CR which could be alternative treatment option in restoring NCCL with better marginal seal and esthetics.